Chick-Erythrocyte Nucleus Reactivation in Heterokaryons: Suppression by Inhibitors of Proteolytic Enzymes - Darzynkiewicz, Zbigniew (1974)
Reactivation of chick-erythrocyte nuclei in heterokaryons (obtained by Sendai virus-induced fusion of chick erythrocytes with HeLa cells) is suppressed by specific inhibitors of trypsin and trypsin-like enzymes. N-α-tosyl-L-lysyl-chloromethane and N-α-tosyl-L-arginine methylester inhibit erythrocyte nuclear enlargement and suppress RNA and DNA synthesis in nuclei of erythrocytes and HeLa cells in heterokaryons at concentrations that only minimally influence individual HeLa cells or HeLa homokaryons. Although other unknown mechanisms of action cannot be formally excluded, the data are interpreted as fitting best with an intracellular site of action of the protease inhibitors studied, and as suggesting a role for cellular proteases in reactivation of chick-erythrocyte nuclei in heterokaryons.